Nucleotide sequence and expression of a Streptomyces griseosporeus proteinaceous alpha-amylase inhibitor (HaimII) gene. - Nagaso, H (1988)
The coding region of the alpha-amylase inhibitor (HaimII) gene from the producing strain Streptomyces griseosporeus YM-25 was localized on an 800-base-pair DNA segment. The nucleotide sequence of a 1,191-base-pair region including the HaimII gene was determined by the dideoxy-chain termination method. The nucleotide sequence data predicted an open reading frame of 363 base pairs starting with an ATG initiation codon and ending with a TGA translational stop codon. The amino acid sequence deduced from the nucleotide sequence indicated that the presumptive pre-HaimII protein extends 37 amino acids to the amino terminus and 6 amino acids to the carboxyl terminus of the mature HaimII protein. The pre-HaimII protein is believed to be processed both during and after secretion. Two forms of the inhibitor, which have a higher molecular weight than that of the HaimII protein isolated from S. griseosporeus, were partially purified from the culture filtrate of Streptomyces lividans containing the cloned HaimII gene.